(3eOi MLjI GdhSGFd GdJcfhdhLjI GdMOjKI aj EKHGJ GdYbhO GdJLGQjI (B/ s - (3YGjV QGTO YGjV GdeQis; (3SejMI GdbdjhHj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI, s, 1998)
(3JHOC GdQSGdI HHGH JegjOj Yf bhGYO GdEKHGJ aj GdehGO GdJLGQjI, Ke Edi bSejf, GdbSe GdChd Yf OQGSI GdhSGFd GdJcfhdhLjI GdMOjKI habG ddeaGgje GdJbdjOjI, Ke GdbSe GdKGfj Yf GdEKHGJ HGdhSGFd GdJcfhdhLjI GdeJbOeI habG ddeaGgje GdMOjKI(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI , (B1998.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B417 - 458.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdEKHGJ GdJLGQjs; (3GdhKjbI GdEdcJQhfjIs; (3GdJhbjY GdEdcJQhfjs; (3GdYbhO GdfehPLjIs; (3GdJLGQI GdEdcJQhfjI GdOhdjIs; (3GdMGSH GdEdcJQhfjs; (3eHOC KHhJ GdcJGHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs